Suppression of PINK1 autophosphorylation attenuates pilocarpine-induced seizures and neuronal injury in rats - Yujie Zhai; Yi Yuan; Yaru Cui; Xiaoqian Wang; Hua Zhou; Qian Teng; Hongjin Wang; Bohan Sun; Hongliu Sun; Jianhua Tang (Brain Research Bulletin)
PTEN-induced kinase 1 (PINK1) autophosphorylation triggers the PINK1/Parkin pathway, which is the main mitophagic pathway in the mammalian nervous system. In the present study, we aimed to mechanistically explore the role of PINK1 in pilocarpine-induced status epilepticus (SE) in Sprague-Dawley rats. Evidence from immunohistochemistry, western blotting, biochemical assays, and behavioral testing showed that pilocarpine-induced SE led to increased levels of PINK1 phosphorylation, mitophagy, mitochondrial oxidative stress, neuronal damage and learning and memory deficits. Using shRNA interference to suppress the expression of translocase outer mitochondrial membrane 7, a positive regulator of PINK1 autophosphorylation, lowered the increased levels of phosphorylated PINK1 following pilocarpine administration. It also reduced the levels of mitophagy, mitochondrial oxidative stress and neuronal damage, and attenuated seizure severity and cognitive deficits. In contrast, suppressing the expression of overlapping with the m-AAA protease 1 homolog, a negative regulator of PINK1 autophosphorylation, led to higher levels of phosphorylated PINK1 following pilocarpine administration. It also led to more serious mitophagy, neuronal damage, as well as worsened seizure severity and cognitive deficits. Our results indicate that PINK1 autophosphorylation plays a vital role in epileptic seizures and neuronal injury by mediating mitophagy. Regulating PINK1 autophosphorylation may change the adverse consequences of epilepsy, and may be an effective neuroprotective strategy.